An Academic Resilience Scale And Model For Malaysian Adolescents - Kuldas, Seffetullah (2018)
Despite their socioeconomically-disadvantaged backgrounds, which impede academic achievements of the majority, some adolescents can academically succeed. This exceptional achievement, defined as academic resilience, raises the question: what and how individual, familial, and school factors enable some adolescent students to perform the same task better than their peers from the same socioeconomic status (low SES). To enhance understanding of this question and to explore factors underlying academic resilience from the local sociocultural frame of reference, this quantitative research integrated various theoretical and empirical literature into a “Socio-Eco-Cultural-Transactional Framework of Academic Resilience”. Using this framework, an academic resilience scale and model for Malaysian adolescents was developed. Reliability and validity of the scale and model were tested and established through pilot and main studies on academic resilience of adolescents with low SES in a rural area of Kedah, Malaysia. The participants were randomly selected through a venue-day-time sampling technique. Using FACTOR 10.7 version, a Minimum Rank Factor Analysis of data collected from pilot study 2 (N = 308) and 4 (N = 127) identified two interpersonal resources and two intrapersonal assets of academic resilience. The resources appeared to be “perceived parental care” and “perceived teacher care”, while the assets appeared “academic performance goal” and “educational optimism”.